FORMATION OF THE PROFESSIONAL READINESS OF THE FUTURE TEACHERS OF IMITATIVE ART (Pedagogy of Higher and Secondary Education, 2007)
The article smooth the problem ofprofessional preparation of the future teachers of imitative art in the process study «Pedagogical drawing».
Keywords: visual aids; pedagogical drawing; professional skills; methodical preparation